Distributive Politics in Developing Federal Democracies: Compensating Governors for Their Territorial Support - Gonzalez, Lucas Isaac (2015)
Using original data from the period 1999–2011 on federal infrastructure investment for all subnational units in two federations, Argentina and Brazil, and a unitary nation, Colombia, this study shows that in developing federal countries with strong governors, presidents use nonearmarked transfers as a tool to compensate governors for sizable and secure territorial political support. The study argues that in these cases, resources do not make electoral power but chase it. In the unitary case, conversely, governors do not influence distributive politics. Variation also was found in the relevance of Congress, legislative overrepresentation, and programmatic criteria across cases. The article discusses possible reasons for these results and their implications for the comparative debate on distributive politics.